The risk of Rift Valley fever virus introduction and establishment in the United States and European Union - Alicia I Rolin; Lea Berrang-Ford; Manisha A Kulkarni (Emerging Microbes and Infections)
Rift Valley fever virus (RVFV) is an arthropod-borne disease resulting in severe morbidity and mortality in both human and ruminant populations. First identified in Kenya in 1930, the geographical range of RVFV has been largely constrained to the African continent, yet has recently spread to new regions, and is identified as a priority disease with potential for geographic emergence. We present a systematic literature review assessing the potential for RVFV introduction and establishment in the United States (US) and European Union (EU). Viable pathways for the introduction of RVFV include: transport of virus-carrying vectors, importation of viremic hosts and intentional entry of RVFV as a biological weapon. It is generally assumed that the risk of RVFV introduction into the US or EU is low. We argue that the risk of sporadic introduction is likely high, though currently an insufficient proportion of such introductions coincide with optimal environmental conditions. Future global trends may increase the likelihood of risk factors for RVFV spread.